The ?-Al2O3 microparticles drive decreasing effects on the sperm quality of rainbow trout - Ozgur, M. E.; Ulu, A.; Ozcan, I.; Balcioglu, S.; Noma, S. A. A.; Ates, B.; Koytepe, S. (Hellenic Veterinary Medical Soc, 2024)
This work examined the effects of alpha-alumina microparticles (alpha-Al2O3-MPs) on the reproductive efficiency of rainbow trout, Oncorhynchus mykiss sperm cells. The alpha-Al2O3-MPs (similar to 100 nm) were characterized by Fourier Transform Infrared Spectrometer, X-ray spectrum and Scanning Electron Microscope. After exposure with alpha-Al2O3- MPs (0.125, 0.25, 0.5, 1.0, and 5.0 g/L 24 h, in vitro) on sperm cells, it was determined to the motility parameters and total glutathione (tGSH) and superoxide dismutase (SOD) as biochemical parameters of sperm cells. The velocities ofsperm cells decreased after exposure to a 0.125 g/L dose of alpha-Al2O3-MPs. However, while the tGSH levels increased in a dose-dependent manner alpha-Al2O3-MPs, the SOD activities decreased. All these changes were significant (p < 0.05) in 1 g/L dose of alpha-Al2O3-MPs when compared with the control group. Finally, we provide a basis for understanding of alpha-Al2O3-MPs toxicity in this study. So, it may be enabled the assessment of risks associated with alpha-Al2O3-MPs pollution in aquatic environment, and allow better predictions of the hazardous properties of similar materials in the future.
Keywords: Alpha-Alumina microparticles; Oncorhynchus mykiss; Reproduction toxicity